Professional Training of Future Educators for the Usage of Ethnological-Aesthetic Means in Work with Children of Senior Preschool Age - Tamara Marchii-Dmytrash; Galyna Boryn (Vasyl Stefanyk Precarpathian National University, 2022)
The relevance of professional training of future educators of IPE (institution of preschool education) for usage ethnological-aesthetic means in work with children is substantiated in the article. The concept of "means" is concretized and a complex of ethnological-aesthetic means, effective for the forming in preschool age children's ideas about culture, life, traditions, customs, rites of the Ukrainian people and aesthetic taste (folk toys, crafts and handicrafts, state and folk symbols, everyday life, arts and crafts) is proposed. Importance of involving senior preschool age children in folk crafts and handicrafts, arts, making folk toys is actualized, which promotes patriotism, development of personal qualities such as kindness, compassion, courage. The role of aesthetics of everyday life, state and national symbols in awareness of the beauty of the surrounding reality by child is determined. The paper suggests theoretical and methodological aspects of professional training of students for decorative drawing and decorative application classes (drawing and application of Easter eggs on planar forms, Yavoriv toys, exercises in elements of Hutsul and Petrykivka painting), making a folk toys from various materials (threads, fabric, hay, straw), modeling visits to a virtual museum in work with senior preschool age children; the importance of such classes for mental, speech development, preparation for schooling of senior preschool age children is substantiated. The pedagogical conditions for the effectiveness of the usage of ethnological-aesthetic means in the practice of institutions of preschool education are proposed. The authors emphasize the importance of training future educators to create an appropriate educational environment, develop skills to select tools and methods for work with children that would promote their creative attitude to the aesthetic development of reality, reflecting it in their own creative activities.